In vitro effects of N-acetylcysteine alone and combined with tigecycline on planktonic cells and biofilms of Acinetobacter baumannii - Feng, Jinlun; Liu, Baomo; Xu, Junwen; Wang, Qinqin; Huang, Lixia; Ou, Weijun; Gu, Jincui; Wu, Jian; Li, Shaoli; Zhuo, Chao; Zhou, Yanbin (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Acinetobacter baumannii (A. baumannii), as a common opportunistic pathogen, has strong ability to form biofilms, which has led to drug resistance and chronic infections. The combination of N-acetylcysteine (NAC) and tigecycline (TGC) was demonstrated to synergistically inhibit biofilm-associated bacterial infections, including methicillin-resistant Staphylococcus aureus and Staphylococcus epidermidis. The purpose of this study is to investigate the effect of NAC and TGC on planktonic cells and biofilms of A. baumannii. Methods: Minimum inhibitory concentrations (MICs) of NAC were determined by broth microdilution method. Biofilm susceptibility was assessed by crystal violet stain. Interactive effects of NAC and TGC on planktonic cells were determined by checkerboard MIC assay. Viable cell count was used to evaluate the combined effect of NAC and TGC on biofilm-embedded bacteria. Results: MICs of NAC against 25 A. baumannii isolates ranged from 16 to 128 mg/mL. NAC alone (0.5–128 mg/mL) significantly inhibited biofilm formation and disrupted preformed biofilms. The combination of NAC and TGC induced a partial synergistic effect (60%) and additive effect (28%) on planktonic bacteria. For biofilm-embedded bacteria, treatment with 16 mg/mL NAC alone or 2 μg/mL TGC alone resulted in significant bactericidal effects (P